STUDI MANAJEMEN DAN REKAYASA LALU LINTAS SIMPANG BERSINYAL DI JALAN RAYA PEKAYON KOTA BEKASI - Siti Khodijah; Syafrin Liputo; Yana Tatiana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Transportation is one type of movement that occurs in life in carrying out every activity; however, in large cities, transportation problems such as traffic jams frequently occur. One among them is Bekasi City, where one of the crossroads in the CBT area of Bekasi City, particularly the signalized intersection of Jalan Raya Pekayon, Bekasi City, is facing extreme traffic. During peak hours, the volume of traffic flow causes a backlog of vehicles on the road at each leg of the crossroads. Based on the problem description, this study will look into the management and engineering of signalized intersection traffic on Jalan Raya Pekayon. This study uses a quantitative method with analysis based on the 2014 Indonesian Road Capacity Guidelines. The results show that the number of cycle times and the condition of the current phase at the intersection are still less effective, owing to the intersection's performance assessment, especially the degree of saturation, delays, and queues, which are still very high. However, after analyzing the proposed problem-solving scenario in Scenario 2, there is an increase in intersection performance with a decrease in delays of 89.80% (weekdays), 75.31% (weekends), queues of 87.21% (weekdays), and 68.78% (weekends).